Rekontruksi Sejarah Lokal sebagai Alternatif Materi Pelajaran Membaca - Dewi, Yusra; Salim, Agus (Jurnal Ilmiah Dikdaya, 2022)
This study aims to reconstruct the local history of the â€œPerang Pantaâ€ as an alternative to the reading subject matter. The approach used is a historical and sociological approach to achieve this goal. The research method is a heuristic method. The research data are from reading texts that explain local history in the form of the â€œPerang Pantaâ€ that took place in Nagari Sariak, Agam Regency, West Sumatra Province. The data source is a research report in the form of a scientific paper with the title "The Problem of the Sariak People's Struggle Against the Dutch". Published in 1982.Publisher SMA Negeri 1 Bukittinggi. Informants in this study played a role in providing the primary source in the form of research reports (scientific papers) which were entered into the office of Wali Nagari Sariak, there were two research informants. First, Ninik Mamak, who knew the history of the â€œPerang Pantaâ€ and archived it, namely Mr Junaidi Dt. Bandaro Gadang, 65 years old. Employment of Former Wali NagariSariak for the 2018 â€“ 2020 period, Retired Principal, Chair of the Sariak Bamus Nagari for the 2014-2020 period, Secretary for the Nagari Customary Density 2020 â€“ 2025, Chair of the 2018-2023 Religious Education Council, Agam Regency level, West Sumatra Province. Second, Wali Nagari Sariak whose name is Ismet Dianto is 41 years old. With the results of the research, the book "History of the Perang Panta" is appropriate to be used as alternative reading material.